PENAMBAHAN ABU DAUN BAMBU SEBAGAI SUBSTITUSI MATERIAL SEMEN TERHADAP KINERJA BETON - Anita Intan Nura Diana; Subaidillah Fansuri; Dwi Deshariyanto (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
Bamboo leaf ash has reactive properties that can react to hard and stiff materials. Based on research, through burning for 2 hours bamboo leaf ash has 75.9% silica. Based on the background, the purpose of this study is to determine the effect of bamboo ash as a mixture of cement on the performance of concrete. The method used in this research is the experimental method. Experiments were carried out on normal concrete with K 240 concrete quality which the variation of bamboo leaf ash is 0%, 3%, 5%, and 7% from the cement mixture and compressive strength test with a sample of 3 cube-shaped specimens measuring 15 x 15 x 15 cm at the age of 14 days. The data analysis technique used is linear regression using SPSS software. The results show the compressive strength value which is influenced by the variation of the mixture of bamboo leaf ash is Y = 13.871 + 0.419 X where x is the variation of the mixture and y is the compressive strength value of concrete. The value of t-test = 2.504 > t-table = 1.812 indicates a significant influence between the addition of variations in the mixture of bamboo leaf ash to compressive strength. The optimum variation was found in the proportion of bamboo ash mixture of 5% and 7%.